PERFORMANCE VERY SMALL APARTURE TERMINAL (VSAT) DALAM KOMUNIKASI DATA - Dali, Sri Wahyuni (Sainstek, 2008)
VSAT (Very Small Aparture Terminal) or micro earth station is the telecommunications used data communications network between computer through satellite constructively by controller station with antenna; diameter of 1,8 m and also the form small and easyly installation at every user location. This research evaluate usage of network VSAT so that inferential in the end how far usage ofd data communications network evaluated from transmission media VSAT used and from this research can give the picture situation of the network use VSAT so that can give the data support for pengatran system performance and planning of network capacities in future. This research use the reference - the reference that relevance with VSAT and collect data of companies/ related/relevant institution as reference in analysing the data (throughput and delay) so that yield the information sistimatis concerning the network performance handal. This research result throughput VSAT canal is 0,32 or 32% and delay is 0,318 second for successful package ( free collision) and also to once remanding have delay 1,838 second.